2010
DOI: 10.1002/pst.450
|View full text |Cite
|
Sign up to set email alerts
|

Planning a Bayesian early‐phase phase I/II study for human vaccines in HER2 carcinomas

Abstract: Recent innovative statistical approaches for phase I/II clinical trials allow one to jointly model the toxicity and efficacy of a new treatment, taking into account the information gathered during the trial. Prior probabilities are then updated with interim data and thus predictive probabilities become more accurate as the trial progresses. In this study, prior distribution elicited from a physician's opinion on the available dose levels planned for a vaccination dose-finding trial, with human DNA in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In this manuscript, we exploit the results on response probability of DNA anti‐HER2 vaccine to build the design prior, and we use historical data, in terms of summary measures from phase I clinical trials identified in a systematic review, to derive the analysis prior.…”
Section: Motivating Example: Dna Vaccination In Her2 Carcinomasmentioning
confidence: 99%
See 2 more Smart Citations
“…In this manuscript, we exploit the results on response probability of DNA anti‐HER2 vaccine to build the design prior, and we use historical data, in terms of summary measures from phase I clinical trials identified in a systematic review, to derive the analysis prior.…”
Section: Motivating Example: Dna Vaccination In Her2 Carcinomasmentioning
confidence: 99%
“…Probabilities of efficacy elicited from 13 translational researchers and physicians for the phase I/II trial on DNA vaccination in HER2 carcinomas form the design prior. Details of the elicitation process are given in Zohar et al By exploiting the same methodology used for the analysis prior, ψ = 0.38 (estimated best fit) gives the best fit design prior (Figure 3), whereas ψ = 4 gives the flat design prior (Figure 3).…”
Section: Motivating Example: Dna Vaccination In Her2 Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, methods were proposed that allow using external information into the dose-finding design, where either external data were used for choosing the skeleton (working model) of the design or for calibrating the prior of the dose-toxicity relationship parameter(s). 16,17 Liu et al proposed using a Bayesian model averaging (BMA) dose-finding method in which the estimated probabilities of toxicity at the end of the previous trial are used to build three different skeletons, that will be averaged during the present trial. 18 Takeda and Morita defined a "historical-to-current" (H-C) parameter representing the degree of borrowing based on a retrospective analysis of previous trial data.…”
Section: Introductionmentioning
confidence: 99%
“…For example, randomized phase I study designs have been proposed for optimizing the dose level or the schedule of therapeutic cancer vaccines . In a nonrandomized setting, Zohar et al proposed a Bayesian “up‐and‐down” phase I design for a cancer vaccine that makes dose level escalation decisions after each patient …”
Section: Introductionmentioning
confidence: 99%